2002
DOI: 10.1001/archderm.138.7.885
|View full text |Cite
|
Sign up to set email alerts
|

Routine vs Extensive Malignancy Search for Adult Dermatomyositis and Polymyositis

Abstract: To identify potential risk factors and the yield of routine screens for early detection of malignancy associated with dermatomyositis (DM) and polymyositis (PM). Design: Retrospective study of malignancies in all patients with DM or PM followed up between the years 1981 and 2000 and a review of the relationship of DM and PM to malignancy, the usefulness of various tests or examinations for malignancy search, and the patients' course. Setting: Departments of internal medicine and dermatology in a teaching hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 40 publications
6
79
0
6
Order By: Relevance
“…How the inflammatory myopathy patients should be assessed for possible cancers is still a matter of debate (23)(24)(25)(26). Surprisingly, the place of tumor markers assays for the search of occult malignancies in dermatomyositis and polymyositis has been poorly assessed (8,27).…”
Section: Discussionmentioning
confidence: 99%
“…How the inflammatory myopathy patients should be assessed for possible cancers is still a matter of debate (23)(24)(25)(26). Surprisingly, the place of tumor markers assays for the search of occult malignancies in dermatomyositis and polymyositis has been poorly assessed (8,27).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that patients with these features may benefit from a more extensive search for malignancy, namely CT of the chest, abdomen, and pelvis. 134 Glucocorticoids are the mainstay of treatment for dermatomyositis, but paraneoplastic dermatomyositis often requires additional immune-modulating therapies. 100 In most cases, successful tumor-directed therapy will also ameliorate symptoms;…”
Section: Acanthosis Nigricansmentioning
confidence: 99%
“…8,9 However, the IMACS does not include erythrocyte sedimentation rate (ESR) or C-reactive protein (CRP), which have been used indiscriminately as possible markers of DM and PM activity. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] High ESR levels have been correlated with neoplasia risk [11][12][13][14][15][16] and pulmonary involvement [17][18][19][20][21][22] in inflammatory myopathies. Likewise, high CRP levels seem to be associated with neuropathy risk in this population.…”
Section: -7mentioning
confidence: 99%
“…Likewise, high CRP levels seem to be associated with neuropathy risk in this population. 23,24 However, these studies [11][12][13][14][15][16][17][18][19][20][21][22][23][24] are limited by the fact that ESR and/or CRP were analyzed in patients who had been submitted to chronic use of glucocorticoids and/or immunosuppressants.…”
Section: -7mentioning
confidence: 99%